Penanaman Nilai-nilai Pendidikan Agama Islam Pada Kantin Kejujuran di SMP Negeri 2 Toboali - Stepanie, Eren; Darlis, Andi M; Jauhari, Muhammad Insan (LENTERNAL: Learning and Teaching Journal, 2024)
The background of this research is the students' lack of understanding about honesty as part of the teachings of the Islamic religion and the challenges in monitoring and evaluating students' honesty in managing the canteen independently. The solution to the lack of awareness of honesty in the school environment is the implementation of an honesty canteen program in accordance with Islamic religious values, namely Aqidah, sharia and morals. The aim of this research is to (1) explore and analyze the instillation of Islamic religious education values in the gap in second junior high school in Toboali,(2) to find out the driving and inhibiting factors for the values of Islamic religious education in the implementation of honesty. This research uses a descriptive qualitative method. It is not permissible to carry it out in state junior high schools. The subjects of this research were school principals, Islamic religious education teachers, canteen staff, and students. The collected data was then analyzed using an inductive method which included: data reduction, data presentation and drawing conclusions. The test results show that the honesty canteen program at the two reverse junior high schools has been running well, this is because in its implementation there is an instillation of Islamic religious education values, namely "Aqidah, sharia and morals. The driving factor for instilling Islamic religious education values is the implementation of the honesty canteen program It teaches the value of honesty, directly practicing the teachings of Islam, but there are several obstacles to implementing honesty, namely a lack of supervision and guidance and an unsupportive environment.